(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The disturbution and eco-coenotic pecularities of the rare species Scutellaria verna Besser (included in Red Data Book of Ukraine) to region “Elanetskiy step” nature reserve are shown. The syntaxonomic scheme of the vegetation whith participant it species are present. The study vegetations rating to Festuco-Brometea Br.-Bl. et R.Tx. 1943, in composition All. Potentillo arenariae-Linion czerniaevii Krasova et Smetana 1999.